2018
DOI: 10.1172/jci.insight.97500
|View full text |Cite
|
Sign up to set email alerts
|

Direct recognition of hepatocyte-expressed MHC class I alloantigens is required for tolerance induction

Abstract: Adeno-associated viral vector-mediated (AAV-mediated) expression of allogeneic major histocompatibility complex class I (MHC class I) in recipient liver induces donor-specific tolerance in mouse skin transplant models in which a class I allele (H-2Kb or H-2Kd) is mismatched between donor and recipient. Tolerance can be induced in mice primed by prior rejection of a donor-strain skin graft, as well as in naive recipients. Allogeneic MHC class I may be recognized by recipient T cells as an intact molecule (direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 65 publications
0
32
0
Order By: Relevance
“…Here, we show the control of an already established CD8 + T cell response against hSGCA mediated by both the induction of Tregs and the homing of transgene-specific CD8 + T cells to the liver, where they express PD-1 and LAG3. The exact mechanism driving homing of reactive CD8 + T cells to the liver remains to be elucidated, although recent work from Paul-Heng and colleagues 49 suggests that direct recognition of antigen expressed in the liver by CD8 + T cells via MHC class I is a key mediator of liver tolerance. Thus, it is conceivable that homing of reactive CD8 + T cells to the liver, via MHC class I recognition of the expressed transgene, together with the unique protolerogenic hepatic immune environment, results in the control of cytotoxic responses via T cell exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show the control of an already established CD8 + T cell response against hSGCA mediated by both the induction of Tregs and the homing of transgene-specific CD8 + T cells to the liver, where they express PD-1 and LAG3. The exact mechanism driving homing of reactive CD8 + T cells to the liver remains to be elucidated, although recent work from Paul-Heng and colleagues 49 suggests that direct recognition of antigen expressed in the liver by CD8 + T cells via MHC class I is a key mediator of liver tolerance. Thus, it is conceivable that homing of reactive CD8 + T cells to the liver, via MHC class I recognition of the expressed transgene, together with the unique protolerogenic hepatic immune environment, results in the control of cytotoxic responses via T cell exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, studies performed by Kumar et al (35) and Tay et al (34) showed that low transgene expression in the liver and high avidity of the T cell for the transgene (34) leads to T cell activation after adoptive transfer of transgenic, OVA-specific CD8 + T cells. Along this line, Paul-Heng et al have recently demonstrated in C57BL/6 mice that high liver expression of an intact allogenic MHCI H2-K d molecule allows indefinite survival of an allogenic H2-K d skin graft (27), whereas liver expression of a mutated H2-K d -D227K transgene, which abrogates recognition of intact allogenic MHCI by CD8 + T cells, leads to partial skin graft survival. Consistent with our results, these studies indicate that liver transgene doses and interaction modalities of transgene-specific CD8 + T cells with transduced hepatocytes are critical for their fate.…”
Section: Discussionmentioning
confidence: 99%
“…These features are specific to the combination of transgene and mouse strain under consideration and likely explain differences observed in the literature regarding the potency of liver tolerance examined with different transgenes and mouse strains (31,47). Of importance, Paul-Heng et al showed that direct recognition of hepatocyte-expressed MHCI allogenic antigens is required for tolerance induction and skin engraftment (27). Our results demonstrate that processing of a defined muscle transgene by antigen-presenting cells of the host leads to CD8 + T cell responses, which are tolerized after recognition of hepatocyte-expressed host MHCI transgene complexes, even in presence of preexisting immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, low expression of co-stimulatory molecules on hepatocytes leads to apoptosis of the alloreactive T cells (10). Paul-Heng et al have found that direct recognition of hepatocyte expressed MHC-I alloantigen (cross presentation) is required for tolerance induction, whereas the indirect recognition of the processed and presented allogeneic peptide on MHC-II by CD4 T cells is not sufficient for tolerance induction although it can prolong the graft survival and generate Tregs to promote transplant tolerance (78, 79). Additionally, processing of the soluble antigens into peptide presented by MHC-I is impaired in hepatocytes lacking collectrin, which is an intracellular chaperone protein within the endoplasmic reticulum-Golgi intermediate compartment and positively regulated (80).…”
Section: Interactions Of Hepatocytes and Alloreactive T Cellsmentioning
confidence: 99%